2002
DOI: 10.1016/s0954-6111(02)80019-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulite® technology: pharmacodynamic and pharmacokinetic implications

Abstract: In the drive to replace chlorofluorinated hydrocarbons (CFCs) by alternative more environmentally friendly propellants in pressurized metered dose inhalers (pMDIs), Chiesi has developed new inhalers using Modulite technology. The aim was to obtain CFC-free pMDIs which are equivalent, in terms of safety and efficacy, to the previous CFC devices at the same dose. When beclometasone dipropionate (BDP) and budesonide Modulite formulations were compared to the equivalent CFC products there was no significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 11 publications
6
18
0
Order By: Relevance
“…The MMAD of the glycerol-free and glycerol-containing formulations, measured via ACI stage deposition data, was 2.4 ± 0.1 lm and 2.5 ± 0.2 lm, respectively (n = 3). No significant difference in stage-by-stage deposition or fine particle fraction/ mass was observed between the two formulations used [8,15]. It is important to note, however, that for the mass of drug emitted by both formulations to be similar, the number of particles (and formulation mass, including excipient) would be different.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MMAD of the glycerol-free and glycerol-containing formulations, measured via ACI stage deposition data, was 2.4 ± 0.1 lm and 2.5 ± 0.2 lm, respectively (n = 3). No significant difference in stage-by-stage deposition or fine particle fraction/ mass was observed between the two formulations used [8,15]. It is important to note, however, that for the mass of drug emitted by both formulations to be similar, the number of particles (and formulation mass, including excipient) would be different.…”
Section: Resultsmentioning
confidence: 99%
“…4 lm) [3]. The area under the plasma concentration curve for the BMP in the Modulite formulations was reported to be markedly different than QVAR, but not dissimilar to the CFC formulations even though the MMAD's were different [8]. In addition, the Modulite formulations were shown to have similar clinical outcomes to CFC formulations in terms of Forced Expiratory Volume and morning serum cortisol concentrations [9].…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, the jet orifice diameter was increased, making the spray plume similar to that of CFC. 30,31 Nowadays, BDP-Modulite ® and budesonideModulite ® are available in the international market The advantage of Modulite ® technology is that it bears a striking resemblance to the pMDI that use CFC propellant. This allows the CFC/HFA transition to be more easily planned, since it is not necessary to change the doses used, as pulmonary deposition and absorption are similar to those of CFC-containing pMDI because the particle size is similar.…”
Section: -23mentioning
confidence: 99%
“…There is some evidence to suggest that the targeting of drug deposition from pMDIs containing HFA propellants is not significantly influenced by the addition of a spacer. [11][12][13] In addition, selection of spacer design may also be unimportant for drug delivery to the periphery of the lung. 8,14 Dubus et al showed salbutamol (albuterol) responses were not significantly different between spacer devices when an HFA134a formulation was used.…”
Section: Introductionmentioning
confidence: 99%
“…11 It has also been shown that use of a spacer with or without an HFA formulation did not change the plasma profiles of beclomethasone dipropionate. 12 Hirst et al showed lung deposition of triamcinolone acetonide by mass was similar with (188 µg) or without spacer (175 µg) setup. 13 Williams et al analyzed a wide range of spacer devices across a solution HFA system (beclomethasone valerate) and a suspension system (triamcinolone acetonide).…”
Section: Introductionmentioning
confidence: 99%